The human gut microbiome – a new and exciting avenue in cardiovascular drug discovery. (3rd October 2019) - Du, Yu; Li, Xingxing; Su, Chunyan; Wang, Li; Jiang, Jiandong; Hong, Bin
ABSTRACT: Introduction : Over the past decade, numerous research efforts have identified the gut microbiota as a novel regulator of human metabolic syndrome and cardiovascular disease (CVD). With the elucidation of underlying molecular mechanisms of the gut microbiota and its metabolites, the drug-discovery process of CVD therapeutics might be expedited. Areas covered : The authors describe the evidence concerning the impact of gut microbiota on metabolic disorders and CVD and summarize the current knowledge of the gut microbial mechanisms that underlie CVD with a focus on microbial metabolites. In addition, they discuss the potential impact of the gut microbiota on the drug efficacy of available cardiometabolic therapeutic agents. Most importantly, the authors review the role of the gut microbiome as a promising source of potential drug targets and novel therapeutics for the development of new treatment modalities for CVD. This review also presents the various effective strategies to investigate the gut microbiome for CVD drug-discovery approaches. Expert opinion : With the elucidation of its causative role in cardiometabolic disease and atherosclerosis, the human gut microbiome holds promises as a reservoir of novel potential therapeutic targets as well as novel therapeutic agents, paving a new and exciting avenue in cardiovascular drug discovery.